Political Economy of Nutrition Policy in Senegal - Fox, Ashley M. (World Bank, Washington, DC, 2019)
Senegal has a reputation for having one of the most effective and far-reaching nutritionservice delivery systems in Africa. Chronic malnutrition has dropped to less than 20 percent, oneof the lowest in Sub-Saharan Africa. The reduction in stunting in particular has been deemed a success in Senegal with the prevalence of child stunting one of the lowest in Sub-Saharan Africa in absolute terms (Nene 2017). This success has at least in part been attributed to broad-based government commitment to nutrition, which has grown from US$0.3 million per year in 2002 to US$5.7 million per year in 2015, increasing from approximately 0.02 percent to 0.12 percent of the national budget. Yet concerns remain regarding whether the level of government support for nutrition is sufficient and the degree to which nutrition has been as effectively “mainstreamed” across major line ministries, such as agriculture, education, water and sanitation, socialprotection and health, to support both nutrition-specific and nutrition-sensitive interventions. Moreover, the nutrition field as a whole is characterized by a myriad of actors (international donors, NGOs, and technical support agencies) whose interventions are not well coordinated, leading to duplications of effort and inefficiencies in the provision of services. A series ofexternal shocks, including food shortages stemming from drought, the global financial crisis, and the instability of prices for local foodstuffs since 2007, has revealed the continued need for additional investment in nutrition and better intersectoral coordination of activities to counter cyclical attention to nutrition and a predominant focus on food insufficiency rather than abroader focus on nutrition. To this end, the government of Senegal, through the CLM, is in the process of drafting the new PSMN to develop a reform agenda for the sector. The PSMN will lay out a framework and timeline for the development of a nutrition financing strategy that will requirespecific analysis of the sector spending and financial basis, linking it to the coverage and quality of nutrition services and assessing the contribution of different sectors and actors to the budget. As part of the Analysis & Perspective: 15 Years of Experience in the Development of Nutrition Policy in Senegal series, the World Bank commissioned this report to elaborate the specific political challenges to and opportunities for further raising the profile ofnutrition on the government’s agenda and secure a sustainable effort to reduce maternal and child malnutrition. The nutrition agenda is often prone to political economy challenges when it competes for government support, as the impact of nutritional intervention is neither immediate nor tangible. Though the benefits of proper nutrition are life-long and are foundational to proper growth and development, nutrition can fall by the wayside in policymakers’ inevitably shorter-termoutlook. With this in mind, the objective of this report was to identify the policy and political levers that can be used to foster government leadership and galvanize intersectoral coordination that mainstreams nutrition into government policies and programs and effectively, efficiently, and sustainably delivers nutrition interventions in Senegal.